Parents’ learning in family literacy programming: Findings from a four-year, mixed-methods evaluation - Esther Prins; Carol Clymer; Elisabeth Grinder McLean; JungEun Lee (Adult Education Research Conference, 2024)
This paper reports findings from a mixed-methods evaluation of five family literacy programs in Philadelphia, mainly serving immigrant mothers. The paper focuses on parents' educational, personal, social, and parenting outcomes.
Keywords: adult education; family literacy; intergenerational learning; parental outcomes; evaluation